Implementasi Loose Part Berbasis Bahan Alam Lokal untuk Meningkatkan Kreativitas Anak Usia 4-5 Tahun di RA Hidayatul Islamiyah Tuban - Rifqi Aulia; Ulya Ainur Rofi’ah (Institut Agama Islam Nahdlatul Ulama Tuban, 2025)
This study aims to describe the implementation of loose parts based on local natural materials to enhance the creativity of children aged 4–5 years at RA Hidayatul Islamiyah Tuban. Early Childhood Education plays a crucial role in building the foundation of children’s development, particularly in fostering creative and imaginative thinking skills. Through the loose parts approach, children are encouraged to explore and create using various natural materials such as stones, bamboo, wood, seeds, and seashells. These materials allow children to experiment freely according to their own ideas and imagination, thus stimulating flexible, innovative, and independent thinking.This research employs a qualitative approach with a case study method. Data were collected through observations of children’s play activities, interviews with teachers, principals, and parents, as well as documentation of learning activities. Data analysis was conducted through the stages of reduction, presentation, and conclusion drawing to gain an in-depth understanding of the implementation of loose parts learning based on local natural materials.The results show that the use of loose parts from local natural materials significantly enhances children’s creativity. Children become more active, curious, and able to produce unique creations from simple natural objects. Moreover, this activity fosters environmental awareness and strengthens the connection between learning and real-life experiences. Therefore, loose parts learning using local natural materials is proven to be an effective strategy for developing creativity and ecological awareness in early childhood education.